2011
DOI: 10.1097/ta.0b013e318215b928
|View full text |Cite
|
Sign up to set email alerts
|

Early Lower Extremity Fracture Fixation and the Risk of Early Pulmonary Embolus: Filter Before Fixation?

Abstract: Early lower extremity/pelvis orthopedic fixation is the single independent predictor of EARLY PE in this patient cohort. Venous thromboembolism/PE prevention strategies should be made a priority in this group of patients, including early preoperative institution of anticoagulation prophylaxis. These results suggest that those with contraindications to early anticoagulation may benefit from insertion of retrievable inferior vena cava filters preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In addition, venous thromboembolism events remain all too common, having been shown to complicate injury in up to 0.55% of all trauma admissions. 4 Among posttraumatic patients with isolated sudden-onset respiratory symptoms, the clinical scenario alone is not sufficient to distinguish pulmonary FE from thrombotic embolism, and CT should be promptly performed to correctly recognize the underlying disease. 5 At autopsy, presence of fat can be identified in the lung vessels of 47-100% of patients with skeletal trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, venous thromboembolism events remain all too common, having been shown to complicate injury in up to 0.55% of all trauma admissions. 4 Among posttraumatic patients with isolated sudden-onset respiratory symptoms, the clinical scenario alone is not sufficient to distinguish pulmonary FE from thrombotic embolism, and CT should be promptly performed to correctly recognize the underlying disease. 5 At autopsy, presence of fat can be identified in the lung vessels of 47-100% of patients with skeletal trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of acute DVT in patients with lower extremity fractures can be as high as 65%, with a mortality of 4%-7% (1, 13, 14). Although VCFs have significantly decreased the occurrence of fatal PE (2,15,16), permanent filter insertion is associated with longterm complications such as delayed filter migration, filter fracture, and arteriovenous fistula (7,8). Becker et al (7) reported that without anticoagulant treatment, up to 15.3% patients implanted with a filter developed inferior vena cava obstruction, and even with anticoagulation the occlusion rate was 1.7%.…”
Section: Discussionmentioning
confidence: 99%
“…14,31 We believe this is due to the fact that this analysis focused on a cohort of severely injured patients with evidence of hemorrhagic shock. This population often has a significant multi-system injury burden, including multiple orthopedic injuries.…”
Section: Discussionmentioning
confidence: 99%